Indian Residential Schools and the Internet: Sites of (De)Colonialization ... - Fender, Lukas (Hannover : Leibniz University Hannover, English Department, 2023)
Using the Indian Residential School (IRS) system as an example, this paper examines the internet as a decolonial site. To do so, I will draw on decolonial concepts as well as ideas from spatial theory. Through the analysis of Indigenous-led organizations and a Facebook group dedicated to the collective memory work of the IRS system, I argue that social media platforms can contribute to revitalize culture and foster communal bonds. Amongst others, digital storytelling, the establishment of common symbols, and the organization of joint actions in the offline world have emerged as digital strategies. These are complemented by collecting and sharing memories and educational materials online. ...